A Study of Anita Desai’s Novels Where Shall We Go This Summer: Exploring Marital Discord and Traditional Marriage in Anita Desai's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Anita Desai has explored different aspects of feminine psyche that also includes man-woman relationship. Almost all of her novels are family playmainly concerned with the theme of marital discord between husband and wife. Sita and Raman in Where Shall We Go This Summer Unlike the Western tradition, in the Indian middle class families, the couples generally go through arranged marriages and do not choose each other. Though times have changed, the tradition of negotiated marriage is still very much in vogue. Sita and Raman’s marriage in Where Shall We Go This Summer.